Succession of fungal dynamics and their influence on physicochemical parameters during pig manure composting employing with pine leaf biochar. (February 2020) - Li, Jiao; Bao, Huanyu; Xing, Wenjing; Yang, Jing; Liu, Ruifang; Wang, Xin; Lv, Lihui; Tong, Xiaogang; Wu, Fuyong
Graphical abstract: Highlights: Addition of pine leaf biochar effectively influenced the fungal abundance in compost. Basidiomycota, Ascomycota and Mucoromycota were the main fungal phyla. Ten percent biochar was a potential option to improve compost quality. Fungal communities were significant correlation with physiochemical parameters in compost. Abstract: The effects of pine leaf biochar (PLB) on fungal community during pig manure composting were investigated. Five different doses of PLB [0% (T1), 2.5% (T2), 5% (T3), 10% (T4) and 15% (T5)] were mixed with mixture of pig manure and sawdust (2:1) for 50 days of composting. The present results indicated that fungal diversity increased more obvious in biochar amendment treatments than control (T1) and that the highest was recorded in T4 treatment. Basidiomycota, Ascomycota and Mucoromycota were the most three abundant phyla in all the treatments, while Heterobasidion, Pezoloma, Mucor, Geastrum, Talaromyces and Cystofilobasidium were the richness genera. In addition, network analysis indicated that fungal community abundance was significantly ( p  < 0.05) associated with temperature, pH, CO2 and CH4 emission and the seed germination index. In summary, the 10% PLB amendment (T4) was a potential option to strengthen fungal diversity and improve the composting efficiency as well as compost quality.